ANALYSIS OF THE MEANING OF MORAL MESSAGES IN FILM IS QUITE DIFFERENT - Arcya Komaraputra Pendit (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Film is one of the forms of mass media that serves not only as entertainment but also as a medium for delivering messages, values, and moral teachings through a combination of visual and audio elements. In addition to portraying social realities, film also functions as a means of expression in response to various events and phenomena occurring in society. The moral messages conveyed in films often reflect human behavior and attitudes in everyday life, as well as demonstrate the positive and negative consequences of actions taken. This study aims to examine the meaning of signs and moral values in the film Agak Laen using Roland Barthes’ semiotic approach. Barthes' approach analyzes signs through three levels of meaning: denotation (literal meaning), connotation (emotional or cultural meaning), and myth (ideological meaning shaped by society). This research is qualitative in nature, with data collected through direct observation and literature review. The results of the study show that Agak Laen contains a number of signs that convey moral messages through its narrative and characters. These signs construct myths that reflect cultural and social values in community life.